Development and Validation Method for Simultaneous Analysis of Retinoic Acid, Hydroquinone and Corticosteroid in Cream Formula by High-Performance Liquid Chromatography - Elvi Rahmayuni, Harmita Harmita, Herman Suryadi (Journal of Applied Pharmaceutical Science, 2018)
A simple, precise and rapid reverse phase HPLC-PDA method has been developed and validated for the simultaneous analysis of hydroquinone (HYQ), dexamethasone (DEX), triamcinolone acetonide (TSA), hydrocortisone acetate (HYA), betamethasone valerate (BEV) and retinoic acid (REA) in the cream dosage form. The mixture of HYQ, DEX, TSA, HYA, BEV and REA was separated on Waters X Bridge C18 5 μm column (4.6 mm × 250 mm). All separations were performed with a 2998 Photodiode Array (PDA) detector on 210-400 nm wavelength, 400C at column temperature and flow rate at 1.2 ml/min. The mobile phase was acetonitrile (ACN): 0.1% formic acid with gradient system. The retention times of HYQ, DEX, TSA, HYA, BEV, and REA were found to be 3.69; 9.13; 9.47; 9.96; 14.92 and 21.20. The method showed good linearity with correlation coefficient 0.9990; 0.9991; 0.9984; 0.9991; 0.9997 and 0.9991 over the range of 25-150 μg/ml for HYQ, DEX, TSA, HYA, BEV and REA, respectively. The method was mean recoveries in the range of 99.05 to 100.96% for all analytes. The developed method can be used in the routine analysis of HYQ, DEX, TSA, HYA, BEV and REA in the cream formula, as well as for qualitative interest in cosmetic preparations or for quantitative interest in drug preparations.
Keywords: Cream, Hydroquinone, Retinoic acid, Corticosteroid, Validation, HPLC.